EVALUATION OF POSSIBILITIES TO IMPROVE ACCURACY CHARACTERISTICS FOR ALGORITHMS OF REFINEMENT ANGULAR VELOCITY OF BALLISTIC AND SPACE OBJECTS IN EARLY WARNING RADARS - Sergei V. Kovbasjuk; Felix M. Andreev; Andrei V. Statkus (Sučasnì Informacìjnì Tehnologìï u Sferì Bezpeki ta Oboroni)
The theoretical capabilities and practical recommendations of increasing the both an accuracy of coordinate estimation and reliability of  ballistic and space targets classification by using estimates of range higher order derivatives for surveillance object in early warning radars (EWR) were studied in previous papers of the authors. Nevertheless, the recommendations were not considered as to practical design selection for the algorithm of refinement angular velocity of targets under the criterion of maximum accuracy of target coordinates estimation. Therefore, the article deals with the methodology of comparative evaluation accuracy characteristics of algorithms of refinement angular velocity ballistic and space objects and assessing the level of their improvement through the use of different variants of construction algorithm of increasing the accuracy of range higher order derivatives, including information on the third derivative of distance. By the results of modeling conclusions about choosing the best options for handling data depending on the context and the input